Efektivitas Pengaturan Makananan Selingan Terhadap Penurunan Kadar Glukosa Darah Pasien DM Tipe II di RSUD Kota Salatiga - Fitri, Ida, Ririn Yuliati, S.Si.T., M.Si, Farida Nur Isnaeni, S.Gz., M.Sc Dietisien (2013)
Introduction: Eating habit in DM patients is very important to control blood glucose in preventing further complications. The distribution of eating habit that consist of three main meals and three snack times believes can prevent insulin insufficiency and fluctuations of insulin stability. Objectives: To determine the effectiveness of on time eating schedule in lowering blood glucose levels in type II diabetic patients in RSUD Salatiga. Methods of research: This research is quasi-experimental. Location of the study was in RSUD Salatiga. Subject was 38 patients with type II DM which divided into two groups: group A was given twice snack and group B was given three times snack. Perday, The data includes characteristics of DM patients, fast bloog glucose (FBG) and postprandial blood glucose (PBG) level before and after. Sampling was using consecutive sampling, while statistical analysis was using independent sample t-test. Results:. Characteristics of respondents was 71.9% women, aging <40 years (53.1%).Most of respondents in group A was having hipertension (31.2%) while group B was stroke (25%) . Decrease in blood glucose levels in group A 27.062 mg / dl FBG and 34.88 mg / dl PBG levels while group B 84.375 mg / dl FBG and 101.625 mg / dl PBG. Independent sample t-test showed no significant difference PBG levels between given two and three times a snack Conclusion: setting snack three times in patients with type II DM is more effective in lowering blood glucose levels